Population : an introduction to concepts and issues - Weeks, John Robert, 1944- (Wadsworth Cengage learning, 2012)
Demographics class just got a lot more interesting. POPULATION doesn't just give you the information; it shows you how to use it. From the debate over how to rebuild the Gulf Coast after Hurricane Katrina to what should be done about Social Security and Medicare, POPULATION lets you apply the research yourself. Plus, POPULATION makes studying for the test easier than ever with its built-in study aides.